Atlas of perforator flap and wound healing : microsurgical reconstruction and cases /: microsurgical reconstruction and cases. ([2019]) - Zheng, He-Ping; (Physician), Jian, Lin; Xu, Yong-Qing; Hu, De-Qing
No abstract available